Controlling of dielectrical properties of hydroxyapatite by ethylenediamine tetraacetic acid (EDTA) for bone healing applications - Kaygili, Omer; Ates, Tankut; Keser, Serhat; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2014)
The hydroxyapatite (HAp) samples in the presence of various amounts of ethylenediamine tetraacetic acid (EDTA) were prepared by sol-gel method. The effects of EDTA on the crystallinity, phase structure, chemical, micro-structural and dielectric properties of HAp samples were investigated. With the addition of EDTA, the average crystallite size of the HAp samples is gradually decreased from 30 to 22 nm and the crystallinity is in the range of 65-71%. The values of the lattice parameters (a and c) and volume of the unit cell are decreased by stages with the addition of EDTA. The dielectric parameters such as relative permittivity, dielectric loss and relaxation time are affected by the adding of EDTA. The alternating current conductivity of the as-synthesized hydroxyapatites increases with the increasing frequency and obeys the universal power law behavior. The HAP samples exhibit a non-Debye relaxation mechanism. The obtained results that the dielectrical parameters of the HAp sample can be controlled by EDTA. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Sol-gel preparation; Crystal structure; Dielectric property